Epidemiology of African swine fever at the wildlife-livestock interface of the Gorongosa National Park, Mozambique - Vosloo, Wilna (University of Pretoria, 2015)
Thesis (PhD (Veterinary Tropical Diseases))--University of Pretoria, 2014.